VIGOR BENIH KAKAO (Theobroma cacao L.) PADA BERBAGAI LAMA PENYIMPANAN DAN INVIGORASI - Maemunah Maemunah; Enny Adelina; I.Y. Daniel (Universitas Tadulako, 2009)
The research aims were to determine the cocoa seed vigor of various storage periods and seed invigorant viewed from aspect of seed physiology quality. This research was a two factorial experiment in a completely randomized design. The first factor was the time length of storage consisted of 5 levels: i) Control, ii) 2 week, iii) 4 weeks, iv) 6 weeks, and v) 8 weeks. The second factor was seed invigoration using ZPT consisted of 4 types: i) without ZPT, ii). 0.01 mmol GA3, iii) 0.01 mmol GA3 + 0.1 mmol NAA, and iv) coconut milk. The data obtained was analyzed using variant analysis; the data with coefficient of variation more than 20 % was transformed to x + 0.5 whereas treatment with significant influence was advanced with HSD test with level of 0.05. The research findings showed that a longer period of seed storage led to the reduction of seed vigor. Invigoration with GA3 + NAA also contributed to a better seed vigor though it was not significantly different from GA3 invigoration and coconut milk. All seed invigoration treatment (GA3 + NAA and coconut milk) could slow seed deterioration up to 6 week storage.